Genome-wide identification of the class III peroxidase gene family of sugarcane and its expression profiles under stresses - Shang, Heyang; Fang, Linqi; Qin, Lifang; Jiang, Hongtao; Duan, Zhenzhen; Zhang, Hai; Yang, Zongtao; Cheng, Guangyuan; Bao, Yixue; Xu, Jingsheng; Yao, Wei; Zhang, Muqing (Frontiers in Plant Science, 2023)
Introduction Plant-specific Class III peroxidases (PRXs) play a crucial role in lignification, cell elongation, seed germination, and biotic and abiotic stresses. Methods The class III peroxidase gene family in sugarcane were identified by bioinformatics methods and realtime fluorescence quantitative PCR. Results Eighty-two PRX proteins were characterized with a conserved PRX domain as members of the class III PRX gene family in R570 STP. The ShPRX family genes were divided into six groups by the phylogenetic analysis of sugarcane, Saccharum spontaneum, sorghum, rice, and Arabidopsis thaliana. The analysis of promoter cis-acting elements revealed that most ShPRX family genes contained cis-acting regulatory elements involved in ABA, MeJA, light responsiveness, anaerobic induction, and drought inducibility. An evolutionary analysis indicated that ShPRXs was formed after Poaceae and Bromeliaceae diverged, and tandem duplication events played a critical role in the expansion of ShPRX genes of sugarcane. Purifying selection maintained the function of ShPRX proteins. SsPRX genes were differentially expressed in stems and leaves at different growth stages in S. spontaneum. However, ShPRX genes were differentially expressed in the SCMV-inoculated sugarcane plants. A qRT-PCR analysis showed that SCMV, Cd, and salt could specifically induce the expression of PRX genes of sugarcane. Discussion These results help elucidate the structure, evolution, and functions of the class III PRX gene family in sugarcane and provide ideas for the phytoremediation of Cd-contaminated soil and breeding new sugarcane varieties resistant to sugarcane mosaic disease, salt, and Cd stresses.